2011
DOI: 10.5005/johcd-5-1-24
|View full text |Cite
|
Sign up to set email alerts
|

A Survey On Dental Knowledge and Gingival Health of Pregnant Women Attending Government Maternity Hospital, Chennai.

Abstract: Gingival diseases are quite common during pregnancy. Aim: A study was done to determine dental knowledge and gingival health of pregnant women. Materials and Methods: The survey was done on 208 antenatal women attending Government Maternity Hospital, Chennai. The dental knowledge was assessed by a close-ended questionnaire. Oral hygiene and gingival health were assessed using Oral Hygiene Index-Simplified and Gingival Index. Statistical analysis using McNemars Chi Square Test and Karl Pearson's Correlation tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
0
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 6 publications
2
0
0
1
Order By: Relevance
“…On the other hand, it is different for those with a lower level of education, who, as we have seen, tend to brush their teeth more frequently than once or twice a day. A similar result to our study was obtained in the survey conducted by Ganesh et al, which showed that 66% of pregnant women brush their teeth twice a day [ 14 ]. These results could be attributed to the fact that having a higher level of education arouses a greater interest in knowing and understanding other topics that deviate from one’s own interest and therefore they more likely they also have notions in the health sector.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, it is different for those with a lower level of education, who, as we have seen, tend to brush their teeth more frequently than once or twice a day. A similar result to our study was obtained in the survey conducted by Ganesh et al, which showed that 66% of pregnant women brush their teeth twice a day [ 14 ]. These results could be attributed to the fact that having a higher level of education arouses a greater interest in knowing and understanding other topics that deviate from one’s own interest and therefore they more likely they also have notions in the health sector.…”
Section: Discussionsupporting
confidence: 92%
“…Whereas, literature suggest the prevalence of periodontal disease as 40%. Sixty percent of the subjects were aware about the importance of dental evaluation every 6 months and similarly results were reported by Ganesh et al and Thomas et al 14,15 It was found that patients had poor knowledge about perinatal oral health similar to the study conducted by Thomas et al among the expectant mothers to evaluate the knowledge and attitude of expectant mothers about infant oral health and their oral hygiene practices in Mangalore city.…”
Section: Figure 3: Attitude and Behavior Of Study Populationsupporting
confidence: 74%
“…Dalam studi Ganesh. 16 ditemukan hubungan yang signifikan antara umur kehamilan dan gingivitis. Penelitian yang dilakukan oleh Mervi Gusroy.…”
Section: Hubungan Antara Umur Kehamilan Dan Gingivitisunclassified